Metodologías de construcción de índices compuestos: Aportes a partir del Índice de Potencial Competitivo Departamental para Uruguay; Methodology for composite index construction: Contributions from the Departmental Competitive Potential Index for Uruguay - Roberto Horta; Micaela Camacho; Luis Silveira; Lucía Ferreira (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– The objective of the article is to carry out a review of the subject of composite indicators, especially that related to the methodological process associated with their construction, detailing and discussing the various steps linked to said process, using the construction of the Competitive Potential Index Departmental (IPCD) as a reference., an indicator that measures the competitive potential of the Departments (administrative regions) in Uruguay, in order to show a specific case and the options that were taken in its construction, without going into the detailed explanation of said indicator. The main reflection that should be highlighted is the need for transparency in the construction of the index. That is, the strength of the composite index and its usefulness in the future will depend directly on the quality of the information and the justification provided for each of the decisions made by the researcher (or research team) in charge of building the index.
Keywords: C38; C43; 330; Composite indicators; Methodology; Competitiveness; Uruguay